Second duke's the charm - Bateman, Kate (Her Majesty's rebels, 2024)
"Meet Her Majesty's Rebels: three brilliant women who run King & Co., London's most exclusive investigative agency... The wedding-night death of her much older husband left Tess Townsend the Dowager Duchess of Wansford--and still a virgin. Now she and her two best friends investigate London's most scandalous crimes, and while Tess longs to experience physical pleasure for herself, she can't risk losing her treasured independence... Cynical shipping magnate Justin Thornton never expected to inherit a dukedom, but he'll do his duty. When the ravishing woman he kissed at a party turns out to be the Dowager Duchess, Justin sees an obvious solution: a marriage of convenience that will suit them both. But the passion that sparks between them is anything but convenient. As Tess works on a new case at the request of Queen Charlotte, her increasingly suspicious behavior makes Justin question her motives--and her past. The infuriating woman clearly can't be trusted, but Justin doesn't believe in love, so there's absolutely no danger of him falling for his own wife...is there?"--